Contemporary Education of Islamic Teachers: Political Dynamics Between Country And Education - Miftakhul Ilmi Suwignya Putra (Didaktika Religia, 2017)
This article discusses the dynamics of contemporary Islamic education. The goal of Islamic education is to provide human resources based on Islamic values and in accordance with the spirit of Islam. The methods of education and instruction should also be designed to achieve the goal. Any methodology that is not oriented towards achieving the goal will certainly be avoided. Thus, Islamic education is not merely transfer of knowledge, but whether the science given can change attitudes. Within this framework, intensive monitoring should be done by society, including government (state), towards learners' behaviors. The next step is realizing it so that necessary education and curriculum programs are harmonious and sustainable. Islamic higher education institutions should be self-evident and transform themselves to meet the challenges of increasingly competitive and complex era. Islamic universities are considered not marketable anymore in facing global competition. Contemporary education must adjust with the recent technological developments. For that reason, it is necessary to develop an education system with global perspective in order to produce output from higher quality educational institutions, so that they are confident in facing global competition, and put forward interdisciplinary method interconnectedly.